LEXICAL RELATIONS ANALYSIS IN AYI KWEI ARMAH’S THE BEAUTIFUL ONES ARE NOT YET BORN: A DISCOURSE-SEMANTIC PERSPECTIVE - YOKOSSI, Tchorkpa Daniel (My University, 2022)
ABSTRACT This study seeks to examine the discourse semantics of two selected excerpts from Ayi Kwei Armarh’s The Beautiful Ones Are Not Yet Born with a focus on lexical relations. The choice of carrying out this research work stemmed from the desire to probe the writer’s language use in the selected excerpts not only in relation to the context of situation, but also with regards to the context of culture for deep meanings uncovering. The study further looks into how the writer uses lexical items and event sequences such as chains of clauses and sentences to relate his texts consistently to their area of focus. The mixed quantitative and qualitative methodology has been used for the attainment of the research objectives. The analysis has revealed the predominance of the expectancy relations over the other types of lexical relations in both studied texts. Such a linguistic depiction of the excerpts is revelatory of the fact that the novelist has stuck to the subject matter of his texts to allow his readership to keep track with his plot in order to allow them to access his encoded messages easily. The expectancy relation is followed in the ranking order by a large number of antonymy and synonymy relations. This testifies to the author’s richness in English vocabulary and his effort to get his poignant messages across without ambiguity. The research opens up to discourse semantic analyses of references and conjunctive relations for more hidden meanings decoding. Key-words: Discourse, Lexical relations, semantics, SFL
Keywords: Discourse; Lexical relations; semantics; SFL